Book Reviews - Charman , Karen (Journal of Public Pedagogies, 2020)
Trump, the Alt-right and Public Pedagogies of Hate and for Fascism—What is to be Done? Mike Cole, London, Routledge, 2019 Theresa May, The Hostile Environment and the Public Pedagogies of Hate and Threat—the Case for a Future Without Borders Mike Cole, London, Routledge, 2020